Identifying populations of the blue jack mackerel (Trachurus picturatus) in the Northeast Atlantic by using geometric morphometrics and otolith shape analysis - Vasconcelos, Joana; Vieira, Ana R.; Sequeira, Vera; González, José A.; Kaufmann, Manfred; Gordo, Leonel Serrano (Fishery Bulletin, 2018)
The population structure of the blue jack mackerel (Trachurus picturatus, Osteichthyes, Carangi-dae), in the northeast Atlantic is still unknown. To identify any distinct population units, three areas were selected: waters off Madeira, Peniche (mainland Portugal), and the Canary Islands. Knowledge of population structure is an aspect of the population dynamics of a species that is essential to effectively assess the existence of stocks and manage fisheries. In this study, geometric morphometrics and otolith shape analysis were successfully applied for population identification. Multivariate analysis of variance (MANOVA) revealed no body shape differences between males and females in each area studied, and therefore the sexes were combined for the analysis. The results of the discriminant analysis showed that a low misclassification occurred among areas; 78.0% of individuals were correctly classified. MANOVA performed on the otolith normalized elliptic Fourier descriptors revealed significant areal differences, but no difference between sexes. An overall classification success of 73.3% in the canonical discriminant analysis was achieved. These results indicate the usefulness of both otolith and body shape analysis for differentiation of blue jack mackerel stocks from the northeast Atlantic and indicate the existence of at least three distinguishable populations of this species.